2013
DOI: 10.3329/imcj.v6i1.14721
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Analgesic Effects of Glycosmis pentaphylla (Retz.) in Swiss Albino Mice

Abstract: Background and purposes: Glycosmis pentaphylla (Retz.) Correa, a medicinal plant is popularly used as herbal remedy for various ailments in Bangladesh. It was also reported that GP has both anti-hyperglycemic and analgesic effects and being widely used to reduce blood glucose and to alleviate pain for many years in this region though published literatures are scarce. The present study was designed to evaluate whether ethanolic extract of Glycosmis pentaphylla (GP) have antihyperglycemic and analgesic effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…A similar effect on lipid metabolism and hepatic performance was also observed for glibenclamide (Ramesh Petchi and Vijaya, 2012). Another study investigating the effect of the ethanol extract of G. pentaphylla on oral glucose tolerance revealed that the extract (250 and 500 mg/kg body weight) improved post-prandial glucose tolerance by 50.7 and 66%, respectively, after 120 minutes of administration (Khatun et al, 2012).…”
Section: Antidiabetic Activitymentioning
confidence: 54%
See 1 more Smart Citation
“…A similar effect on lipid metabolism and hepatic performance was also observed for glibenclamide (Ramesh Petchi and Vijaya, 2012). Another study investigating the effect of the ethanol extract of G. pentaphylla on oral glucose tolerance revealed that the extract (250 and 500 mg/kg body weight) improved post-prandial glucose tolerance by 50.7 and 66%, respectively, after 120 minutes of administration (Khatun et al, 2012).…”
Section: Antidiabetic Activitymentioning
confidence: 54%
“…Another similarly designed study reported 36.54 and 57.70% reductions in writhing counts for the methanol extract at doses of 250 and 500 mg/kg body weight, indicating prominent dose-dependent analgesic property for the extract (Sarkar et al, 2013). The ethanol extract (500 mg/kg body weight) inhibited the nociceptive response in mice by 75.51%, suggesting that the plant was a potential source of antinociceptive phytoconstituents (Khatun et al, 2012). Further efforts are warranted to identify the underlying mechanism(s) of action of these extracts and screen individual phytoconstituents for antinociceptive activity.…”
Section: Analgesic Activitymentioning
confidence: 99%
“…About 60 Swiss Albino male mice were used for this purpose (weight 20–25 g). The findings show that GP extract has a short and a week-long antihyperglycemic impact comparable to metformin HCl, a recognized and commonly used antihyperglycemic agent [ 125 ].…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%